2021
DOI: 10.1186/s12967-020-02694-1
|View full text |Cite
|
Sign up to set email alerts
|

ER resident protein 44 promotes malignant phenotype in nasopharyngeal carcinoma through the interaction with ATP citrate lyase

Abstract: Background Nasopharyngeal carcinoma (NPC) is one of the most common malignancy in head and neck. With the development of treatments, the prognosis has improved these years, but metastasis is still the main cause of treatment failure. The endoplasmic reticulum (ER) resident protein 44 is a UPR-induced ER protein of the protein disulphide isomerase (PDI) family. This study investigated the role of ERp44 in NPC progression. Methods Firstly, immunohist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 38 publications
2
6
0
Order By: Relevance
“…In addition, we used transparent in vivo imaging analysis of tumor metastasis [ 31 , 32 ] by microinjecting Dil-labeled, stably transfected oral cancer cell lines into the perivitelline space of Tg (fli-1: EGFP) zebrafish for 3 days to observe cell invasion (Fig. 1L ).…”
Section: Resultsmentioning
confidence: 99%
“…In addition, we used transparent in vivo imaging analysis of tumor metastasis [ 31 , 32 ] by microinjecting Dil-labeled, stably transfected oral cancer cell lines into the perivitelline space of Tg (fli-1: EGFP) zebrafish for 3 days to observe cell invasion (Fig. 1L ).…”
Section: Resultsmentioning
confidence: 99%
“…In our previous research, we have also reported that ERp44 was highly expressed in NPC and associated with patients' survive state and clinical stages, it also participated in promoting cells proliferation and migration [22]. However, the role of ERp44 on cell chemoresistance remains unclear.…”
Section: Introductionmentioning
confidence: 98%
“…ERP44 can not only regulate protein maturation and secretion but also participate in the modulation of calcium as well as redox homeostasis in the endoplasmic reticulum [ 26 , 27 ]. In nasopharyngeal carcinoma, the interaction between ERP44 and ACLY promotes the malignant phenotype of nasopharyngeal carcinoma cells [ 28 ]. In addition, ERP44 inhibits the migratory ability of lung cancer cells through IP3R2 [ 29 ].…”
Section: Discussionmentioning
confidence: 99%